Democratic management of public education impacts of the impossibility of the educational administrative technical server competing for the Rector of the Federal Institute of Education, Science and Technology of Mato Grosso (Research, Society and Development, 2020)
The present study intends to discuss the possible repercussions on the democratic management of the public teaching of the IFMT in the face of the impossibility of the civil servants of the administrative technical segment in education to run for the elections for Dean of the Federal Institute of Education, Science and Technology of Mato Grosso, considering that this type of investigative approach seeks to understand the low representativeness of technicians in the General Directorates. The democratic management of public education is a constitutional principle that aims to guarantee the participation of the entire academic community in school management, however it happens that education technicians do not enjoy full rights even though they represent a third of the votes. Thus, this paper aims to discuss how such a restriction impacts the representativeness of the educational administrative technician within the scope of the IFMT. It has as theoretical support the federal and state laws on education, as well as the authors Paro and Luck, among others. Thus, the research concludes that the absence of civil servants from the technical and administrative educational segment is contrary to the principle of democratic management of public education, and reflects on the representativeness of the segment, favoring segregation and increasing the gap between technical servants and teachers.